Grassland Alterations Do Not Affect Breeding Success, But Lead to Dietary Shifts of Eastern Imperial Eagle, a Top Predator: a Case of Successful Adaptation - Dimitar A. Demerdzhiev; Dobromir D. Dobrev; Zlatozar N. Boev; Nedko P. Nedyalkov; Atanas G. Delchev; Stoycho A. Stoychev; Tseno H. Petrov (Пернатые хищники и их охрана)
Habitat transformation is identified as a global threat to biodiversity, affecting threatened raptors. In our study area, habitat change dramatically affected permanent grasslands, shrinking their availability. As we expected, the decrease in share of grasslands in eagles’ territories significantly affected occupancy rate, but not productivity: we found that occupancy rate decreased significantly, while productivity showed no trend. Understanding the adaptive capacity of top predators and how they respond to shifts in prey abundance and availability is crucial for their conservation. We investigated the diet pattern of the endangered Eastern Imperial Eagle (Aquila heliaca) facing long-term and large-scale changes.